If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10+9q=11=8q
We move all terms to the left:
10+9q-(11)=0
We add all the numbers together, and all the variables
9q-1=0
We move all terms containing q to the left, all other terms to the right
9q=1
q=1/9
q=1/9
| 104-z=37.42 | | 3/7+(-2/3x)=1/2 | | 3+p=210 | | -24=b-11 | | 4x-21=5x-3 | | 10r+9=249 | | 3/7+-2/3x=1/2 | | 10x-5+3x=8-3 | | m+24/5=7 | | 8a+4+2a-2=19a+31 | | 8-6(a+)=9+a | | 2n+20=3n+10 | | -4(v-3)=-6v+10 | | (.2x+x)=340 | | n9-(2)=0 | | -15+40=-5(x+3) | | -9x-15=95 | | -27=n-(-24) | | w-70=42 | | 2n7=11 | | 15=3+3p | | -38=-4u+6(u-5) | | F(x)=6x-180 | | 3(4x+7)=-43+28 | | 12=b-15 | | K=-9-2k | | -4y+48=-8(y-3) | | -3z+8+(+2z)=-12 | | 33a+4+35a-2=39a+31 | | 5=6n-5n | | r-(-29)=-57 | | -2+9j=8j |